2020
DOI: 10.1590/1678-4685-gmb-2019-0302
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the complete chloroplast genomes from six Neotropical species of Myrteae (Myrtaceae)

Abstract: Myrteae is the largest and most diverse tribe within Myrtaceae and represents the majority of its diversity in the Neotropics. Members of Myrteae hold ecological importance in tropical biomes for the provision of food sources for many animal species. Thus, due to its several roles, a growing interest has been addressed to this group. In this study, we report the sequencing and de novo assembly of the complete chloroplast (cp) genomes of six Myrteae species: Eugenia brasiliensis, E. pyriformis, E. nitida, Myrci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…The regions LSC, SSC, and IR presented 34.8%; 30.8%, and 42.7% of the GC content respectively. These sizes are similar to those already sequenced for other species of tribe Myrteae (Eguiluz et al, 2017a(Eguiluz et al, , 2017bMachado et al, 2017Machado et al, , 2020Rodrigues et al, 2020;Table S1). A total of 112 different genes were identified: 78 protein-coding, 30 tRNA genes, and four rRNA genes (Table 1).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…The regions LSC, SSC, and IR presented 34.8%; 30.8%, and 42.7% of the GC content respectively. These sizes are similar to those already sequenced for other species of tribe Myrteae (Eguiluz et al, 2017a(Eguiluz et al, , 2017bMachado et al, 2017Machado et al, , 2020Rodrigues et al, 2020;Table S1). A total of 112 different genes were identified: 78 protein-coding, 30 tRNA genes, and four rRNA genes (Table 1).…”
supporting
confidence: 85%
“…Patterns of structural conservation and synteny among six plastid genomes of Myrteae species were also reported by Rodrigues et al (2020). Here we show that such preserved patterns were shared with R. tomentosa, an earlier divergent species within Myrtaceae (Vasconcelos et al, 2017).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…In addition, other chloroplast genomes of Myrtales have been reported recently. Rodrigues et al [ 27 ] compared the structure, gene number and genome size of six chloroplast genomes of Myrtales finding them to be similar to those of other Myrtales species. However, previous studies on chloroplast genomes of Myrtales have not been consistent, with some based on families, genera or species.…”
Section: Introductionmentioning
confidence: 99%
“…The family Myrtaceae stands out (Chrystal et al, 2020;Gatto et al, 2020), found mainly in the southern region of Brazil, which demonstrates the importance of developing research with native fruits (Neri-Numa et al, 2018;Rodrigues et al, 2020), many still little explored (Moreira-Araújo et al, 2019) and with great potential for economic exploration (Lattuada et al, 2019;Neri-Numa et al, 2018). In this family, the Myrcianthes pungens (O. Berg) D. Legrand, popularly known as guabiju, it is a medium to large tree with around 20 m, present simple leaves and considered ornamental plant, its fruits are appreciated due to the pleasant sweet flavor (Assumpção et al, 2017).…”
Section: Introductionmentioning
confidence: 99%